Imaging Evaluation of Dogs and Cats with Dysphagia. (31st October 2012) - Pollard, Rachel E.
Abstract : The current literature is reviewed in this paper regarding the application of diagnostic imaging in the evaluation of swallowing disorders of the dog. The applications of radiography, contrast radiography, and contrast videofluoroscopy are discussed with pertinent case examples provided for emphasis. The indications for image-guided interventions are also described.